2001
DOI: 10.1046/j.0953-816x.2001.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and central nervous system distribution of receptor activity modifying proteins in the rat

Abstract: Calcitonin gene-related peptide (CGRP), adrenomedullin (ADM), amylin and calcitonin (CT) are structurally and functionally related neuropeptides. It has recently been shown that the molecular pharmacology of CGRP and ADM is determined by coexpression of one of three receptor activity-modifying proteins (RAMPs) with calcitonin receptor-like receptor (CRLR). Furthermore, RAMP proteins have also been shown to govern the pharmacology of the calcitonin receptor, which in association with RAMP1 or RAMP3, binds amyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 30 publications
8
79
1
Order By: Relevance
“…Neither 10 nM h␣CGRP nor hAM elicited significant increases in cAMP in nontransfected HEK-293 cells or cells transfected with HA-hRAMP1 or hCRLR alone. On the other hand, the coexpression of hCRLR with HA-hRAMP1 enabled CGRP and AM to each elicit significant increases in cAMP, which is consistent with previous reports that CGRP and AM bind to the CRLR/RAMP1 heterodimer with similar affinities (8,9,12,24,25). Similar CGRPand AM-evoked increases in cAMP levels were seen when hCRLR was co-expressed with D74-76, D105-107, or D109-112.…”
Section: Construction and Characterization Of Hramp1 Deletion Mutants-supporting
confidence: 78%
“…Neither 10 nM h␣CGRP nor hAM elicited significant increases in cAMP in nontransfected HEK-293 cells or cells transfected with HA-hRAMP1 or hCRLR alone. On the other hand, the coexpression of hCRLR with HA-hRAMP1 enabled CGRP and AM to each elicit significant increases in cAMP, which is consistent with previous reports that CGRP and AM bind to the CRLR/RAMP1 heterodimer with similar affinities (8,9,12,24,25). Similar CGRPand AM-evoked increases in cAMP levels were seen when hCRLR was co-expressed with D74-76, D105-107, or D109-112.…”
Section: Construction and Characterization Of Hramp1 Deletion Mutants-supporting
confidence: 78%
“…CLR and RAMP1 were co-expressed, suggesting expression of functional CGRP receptor in fibers within laminae I and II. The presence of receptor components in the spinal cord is supported by the mRNA expression of RAMP1 and RCP, detected with specific oligonucleotides for in situ hybridization [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The current qPCR results provide quantifiable data that support this idea, as mRNA for all components of the amylin receptor complex are expressed within the VTA, including both subtypes of CTR and all three RAMP subtypes. Although further investigation is needed to identify the phenotype(s) of VTA neurons (eg, dopaminergic, GABAergic, glutamatergic) that express the amylin receptor complex, the equivalent expression of the three RAMP subtypes within the VTA contrasts with the prevalence of RAMP1 mRNA expression in the NAc (Oliver et al, 2001), as well as with the prevalence of RAMP2 and RAMP3 in the AP (Barth et al, 2004). Different combinations of RAMP and CTR subtypes create receptor complexes that all bind amylin but also have differing affinities for other calcitonin family ligands such as calcitonin generelated peptide and adrenomedullin.…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary step toward testing a role for VTA amylin receptor signaling in the control of food intake, we used qPCR to identify mRNA expression of the components of the amylin receptor complex in the VTA. In addition, we examined mRNA expression of the two CTR subtypes and the three RAMP subtypes in the NAc core and shell subregions as positive controls, as the NAc expresses amylin receptor complexes consisting primarily of CTR-A and RAMP1 (Oliver et al, 2001;Young, 2005). qPCR analysis revealed that both CTR subtypes and all three RAMP subtypes are expressed in each of the three sites examined, albeit at varying levels of expression.…”
Section: All Components Of the Amylin Receptor Complex Are Expressed mentioning
confidence: 99%